2017
DOI: 10.1007/s13280-016-0866-6
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation phenology gradients along the west and east coasts of Greenland from 2001 to 2015

Abstract: The objective of this paper is to characterize the spatiotemporal variations of vegetation phenology along latitudinal and altitudinal gradients in Greenland, and to examine local and regional climatic drivers. Time-series from the Moderate Resolution Imaging Spectroradiometer (MODIS) were analyzed to obtain various phenological metrics for the period 2001–2015. MODIS-derived land surface temperatures were corrected for the sampling biases caused by cloud cover. Results indicate significant differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Here we consequently use cloud-free data only which are gap-filled based on empirical relationships between estimates of net daily shortwave radiation and LST, as described in ref. 20 . Terra overpasses central Greenland at approx.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we consequently use cloud-free data only which are gap-filled based on empirical relationships between estimates of net daily shortwave radiation and LST, as described in ref. 20 . Terra overpasses central Greenland at approx.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a method to use LST to assess ground temperatures in a larger North Atlantic region was presented, but scarcely validated for sub-regions such as Greenland 13 . Here we use a gap-filled version of MOD11A1 (following 20 ), due to otherwise missing data in cloudy conditions that can cause a significant cold bias 21 . The resulting distribution of LST data across Greenland (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with previous studies that used MODIS datasets after 2000 to analyze vegetation variation [78,79], this study used the GLASS GPP product and revealed the spatiotemporal characteristics of GPP in the GKM from 1982 to 2015. Obviously, an extension of the study period could provide much more information about the dynamic change of vegetation and the carbon cycle.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Each satellite provides an NDVI dataset with a temporal resolution of 16 days and a spatial resolution of approximately 250 m. The data from the two satellites were combined in order to achieve a more complete time series covering years 2001–2017. The data were processed in agreement with Karami et al (), in order to remove the effects of cloud cover and smooth the time series through temporal interpolation of the NDVI. Some modifications were applied to the original algorithm to improve the cloud detection mechanism and to obtain a more realistic seasonal NDVI curve (see Karami et al, ).…”
Section: Methodsmentioning
confidence: 99%